Changes in the expression of voltage-gated sodium channels Nav1.3, Nav1.7, Nav1.8, and Nav1.9 in rat trigeminal ganglia following chronic constriction injury. Issue 12 (17th August 2016) - Xu, Wenhua; Zhang, Jun; Wang, Yuanyin; Wang, Liecheng; Wang, Xuxia
Abstract : Voltage-gated sodium channels (VGSCs), especially the tetrodotoxin-sensitive Nav 1.3 and Nav 1.7, and the tetrodotoxin-resistant Nav 1.8 and Nav 1.9, have been implicated in acute and chronic neuropathic pain. The aim of this study was to investigate the expression of VGSC Nav 1.3, Nav 1.7, Nav 1.8, and Nav 1.9 after nerve injury and their roles in the development of trigeminal neuralgia (TN). We used the infraorbital nerve-chronic constriction injury model of TN in the rat. The time course of changes in the mechanical pain threshold was examined. In addition, real-time PCR and double immunofluorescence staining of VGSC α subunits were used to evaluate messenger RNA and protein expression, respectively, in the trigeminal ganglion. Behavioral tests showed that the mechanical pain threshold decreased significantly 4–42 days after surgery and reached the lowest observed value by day 12. Compared with sham-operated controls, we found that trigeminal ganglion in rats subjected to an infraorbital nerve-chronic constriction injury showed upregulation of Nav 1.3 and downregulation of Nav 1.7, Nav 1.8, and Nav 1.9 messenger RNA and protein levels. Our findings suggest that VGSC may participate in the regulation of TN.